2010
DOI: 10.1088/0022-3727/43/11/115203
|View full text |Cite
|
Sign up to set email alerts
|

Production of molecules on a surface under plasma exposure: example of NO on pyrex

Abstract: We propose a new experimental approach to the study of surface-catalyzed nitric oxide production under plasma exposure. Stable nitrogen species are grafted to the surface of pyrex discharge tube during N 2 plasma pretreatment. These species are trapped by surface active sites and being exposed to O 2 plasma, they initiate production of NO molecules, which are detected using tunable diode laser absorption spectroscopy. Supposing that nitrogen species are adsorbed N atoms, we estimate the initial surface coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…One should mention the elegant spinning wall method proposed by Vincent Donnelly that allows quasi in situ Auger diagnostics of surfaces in contact with low pressure plasmas combined with Langmuir‐Hinshelwood desorption flux measurements. A different technique to measure the coverage of stable chemisorbed nitrogen and oxygen atoms on surfaces under plasma exposure was developed in ref . With this technique, stable chemisorbed N (O) atoms are grafted to reactor walls during a N 2 (O 2 ) plasma pretreatment and then probed in‐situ by exposing the pretreated surface to reactive molecules (e.g., NO, C 2 H 2 ) or to discharges in isotopically enriched 30 N 2 or 36 O 2 .…”
Section: Model Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…One should mention the elegant spinning wall method proposed by Vincent Donnelly that allows quasi in situ Auger diagnostics of surfaces in contact with low pressure plasmas combined with Langmuir‐Hinshelwood desorption flux measurements. A different technique to measure the coverage of stable chemisorbed nitrogen and oxygen atoms on surfaces under plasma exposure was developed in ref . With this technique, stable chemisorbed N (O) atoms are grafted to reactor walls during a N 2 (O 2 ) plasma pretreatment and then probed in‐situ by exposing the pretreated surface to reactive molecules (e.g., NO, C 2 H 2 ) or to discharges in isotopically enriched 30 N 2 or 36 O 2 .…”
Section: Model Formulationmentioning
confidence: 99%
“…Recombination probabilities measured in mixtures (e.g., N 2 /O 2 ) are usually different from those observed in pure gases . Moreover in mixtures, recombination between chemically different atoms may take place, as for example production of NO from recombination of O and N on the surface . Chemically different atoms may interact differently with surface active sites which further complicates theoretical description of surface kinetics in gas mixtures.…”
Section: Further Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that N and O recombination produces spontaneously emitted luminescence via the reaction O + N → NO, N + NO → N 2 + O, but such processes occur mostly under appropriate thermal conditions (14,15) and are unlikely to explain TL which proceeds only on stimulation. On the other hand, nitrogen implantation in diamond produces a point defect consisting of a substitutional nitrogen atom adjacent to a vacancy (16).…”
Section: Discussionmentioning
confidence: 99%
“…There are two main mechanisms to be discussed within gas-phaseN TPNF to synthesize NO x , [25] which are i) catalytic surfacea bsorption of nitrogen followed by the reaction of other absorbed or gaseous species and ii)plasma dissociation followed by gaseous reactions. There are two main mechanisms to be discussed within gas-phaseN TPNF to synthesize NO x , [25] which are i) catalytic surfacea bsorption of nitrogen followed by the reaction of other absorbed or gaseous species and ii)plasma dissociation followed by gaseous reactions.…”
Section: Introductionmentioning
confidence: 99%